Gringolandia : a novel - Miller-Lachmann, Lyn, 1956- (Willimantic, CT : Curbstone Press, 2009)
In 1986, when seventeen-year-old Daniel's father arrives in Madison, Wisconsin, after five years of torture as a political prisoner in Chile, Daniel and his eighteen-year-old "gringa" girlfriend, Courtney, use different methods to help this bitter, self-destructive stranger who yearns to return home and continue his work.
Includes bibliographical references (p. [281]).
Keywords: Fathers and sons -- Fiction; Political activists -- Fiction; Chile -- Politics and government -- 1973-1988 -- Fiction; Post-traumatic stress disorder -- Fiction; Journalists -- Fiction; Chilean Americans -- Fiction; People with disabilities -- Fiction; Madison (Wis.) -- Fiction; Historical fiction; Young adult fiction; Proofs (Printing)